2022
DOI: 10.1111/2041-210x.13975
|View full text |Cite
|
Sign up to set email alerts
|

Extending isolation by resistance to predict genetic connectivity

Abstract: Genetic connectivity lies at the heart of evolutionary theory, and landscape genetics has rapidly advanced to understand how gene flow can be impacted by the environment. Isolation by landscape resistance, often inferred through the use of circuit theory, is increasingly identified as being critical for predicting genetic connectivity across complex landscapes. Yet landscape impediments to migration can arise from fundamentally different processes, such as landscape gradients causing directional migration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…S3 ). In this situation, net visitation rates quantify the expected net movement rates of dispersing individuals through a given pixel in a landscape based on specific starting and ending locations ( 34 ). Both mortality and conflict together reduced expected movement and connectivity between key populations, decreasing predicted net visitation rates ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3 ). In this situation, net visitation rates quantify the expected net movement rates of dispersing individuals through a given pixel in a landscape based on specific starting and ending locations ( 34 ). Both mortality and conflict together reduced expected movement and connectivity between key populations, decreasing predicted net visitation rates ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we mapped the predicted movement and flow of elephants based under assumptions of no constraints regarding absorption from natural mortality or conflict relative to expectations of flow under human–elephant conflict. To do so, we calculated net visitation rates over space ( 34 ). Visitation rates are the th element of F , which describe the total time a disperser spends at location if starting in location .…”
Section: Methodsmentioning
confidence: 99%
“…Our findings provide several quantified estimates of important aspects for carnivore conservation translocations that can be compared among potential reintroduction or colonization areas by managers for any species. Previously, Fletcher et al (2022) demonstrated the effectiveness of the SAMC framework to predict population structure better than more traditional methods of connectivity analysis, such as least-cost and circuit theory, because of its ability to consider directional movement resistance. Vasudev et al (2023) were able to test SAMC model predictions using conflict data for Asian elephant (Elephas maximus) in a shared landscape and found that accounting for animal movement improved their predictive ability of conflict hotspots, which could then be integrated into the Importantly, the flexibility of the SAMC framework can be tailored to the specifics of any locale and species and can be designed to test model assumptions and assess a wide variety of possible scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the areas occupied by wolves, the SAMC framework can be updated and expanded (e.g. to include gene flow; Fletcher et al, 2022) to better model wolf recovery as restoration progresses, more empirical data become available, and more specific management goals are developed or policies change (e.g. protection status of wolves federally or in surrounding states).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between organisms and their environment shape fundamental ecological phenomena such as species ranges (Kearney & Porter 2009), population dynamics Kareiva et al 1990), community composition (Menge & Olson 1990), and evolutionary feedbacks . These relationships also provide critical applied insights about, for example, spatiotemporal patterns of biological diversity Woodin et al 2013;Evans et al 2015), population trends Madin et al 2012), or genetic connectivity (Cushman & 3 Lewis 2010;Creel et al 2019;Fletcher Jr et al 2022) -insights necessary to address the twin planetaryscale ecological crises of climate change and biodiversity loss . Therefore, there is significant value in frameworks that can link the relationship between organisms and their environments to their niches (Kearney 2006;Matthiopoulos 2022), and make predictions from such relationships about the distribution of individuals and species geographically Inferring relationships between individuals and their environment has traditionally relied on observations of occurrence patterns over some set of environmental contexts which vary geographically , typically by using environmental dimensions to contrast observations from locations where organisms are putatively absent (Mackey & Lindenmayer 2001;Johnson et al 2006;Moorcroft & Barnett 2008).…”
Section: Introductionmentioning
confidence: 99%